2023
DOI: 10.1097/acm.0000000000005121
|View full text |Cite
|
Sign up to set email alerts
|

Drama Training as a Tool to Teach Medical Trainees Communication Skills: A Scoping Review

Abstract: Purpose Recognizing the similarities between the skills an actor needs and those required of a physician in clinical communication, medical educators have begun to create drama-based interventions to teach communication skills. The purpose of this scoping review was to summarize existing educational interventions that use drama training to teach medical trainees communication skills. Method The authors searched PubMed, CINAHL Plus, Embase, ERIC, and Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(191 reference statements)
0
1
0
Order By: Relevance
“…A recent scoping review, examining 30 articles published between 2020 and 2022, reported that improv and other theater techniques positively impact communication skills among healthcare providers. 5 Nine of the articles reported on interventions that taught improv techniques to medical students exclusively, 6-14 and seven were multiweek courses. [7][8][9][10][11]13,14 Although single workshops have shown positive results, concerns remain about the degradation of single-session communication skills over time.…”
mentioning
confidence: 99%
“…A recent scoping review, examining 30 articles published between 2020 and 2022, reported that improv and other theater techniques positively impact communication skills among healthcare providers. 5 Nine of the articles reported on interventions that taught improv techniques to medical students exclusively, 6-14 and seven were multiweek courses. [7][8][9][10][11]13,14 Although single workshops have shown positive results, concerns remain about the degradation of single-session communication skills over time.…”
mentioning
confidence: 99%